2020
DOI: 10.1103/physrevlett.124.221103
|View full text |Cite
|
Sign up to set email alerts
|

Ice Coverage of Dust Grains in Cold Astrophysical Environments

Abstract: Surface processes on cosmic solids in cold astrophysical environments lead to gas phase depletion and molecular complexity. Most astrophysical models assume that the molecular ice forms a thick multilayer substrate, not interacting with the dust surface. In contrast, we present experimental results demonstrating the importance of the surface for porous grains. We show that cosmic dust grains may be covered by a few monolayers of ice only. This implies that the role of dust surface structure, composition, and r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…A recent study of UV irradiation of H 2 /CO codeposited mixtures showed rich chemistry for this system owing to the interaction of an electronically excited CO molecule and the H 2 molecule (Chuang et al 2018). Moreover, very recent results are inverting the trend of considering several onion-like models of cold ices (Marchione et al 2019;Potapov et al 2020). This new set of experiments shows that small icy domains (clusters or islands) are deposited on top of the refractory phase with voids in between.…”
Section: Astrophysical Implicationsmentioning
confidence: 89%
“…A recent study of UV irradiation of H 2 /CO codeposited mixtures showed rich chemistry for this system owing to the interaction of an electronically excited CO molecule and the H 2 molecule (Chuang et al 2018). Moreover, very recent results are inverting the trend of considering several onion-like models of cold ices (Marchione et al 2019;Potapov et al 2020). This new set of experiments shows that small icy domains (clusters or islands) are deposited on top of the refractory phase with voids in between.…”
Section: Astrophysical Implicationsmentioning
confidence: 89%
“…However, recent laboratory studies have shown that the bare dust material would be available for the surface processes in cold astrophysical environments. The experiments on the agglomeration of H2O molecules on the dust surface by Rosu-Finsen et al and Marchione et al [47,48] and on the thermal desorption of H2O and CO ices mixed with dust grains by Potapov et al [49,50] clearly demonstrate this finding. Cosmic dust grains may be covered by a submonolayer or few layer quantities of ice due to their fractal nature, high porosity and corresponding large surface area (see ref.…”
Section: Laboratory Astrophysicsmentioning
confidence: 86%
“…Cosmic dust grains may be covered by a submonolayer or few layer quantities of ice due to their fractal nature, high porosity and corresponding large surface area (see ref. [50] for a discussion). In addition, agglomeration of H2O molecules may result in grain surfaces presenting both wet and dry areas even for a "thick" ice mantle.…”
Section: Laboratory Astrophysicsmentioning
confidence: 99%
“…On planet Earth, through hydrogen bonding between water monomers, stable water nanoclusters, both neutral and ionized, are easily formed in molecular beams (Carlon, 1981), occur naturally in the water vapour of earth's atmosphere (Aplin and McPheat, 2005), and are produced from amorphous ice by energetic ion bombardment (Martinez, 2019). In the cosmos, therefore, a natural route to water nanocluster formation would be via the ejection from amorphous water-ice coatings of cosmic dust grains (Dulieu et al ., 2010; Potapov et al ., 2020), which are believed to be abundant in interstellar clouds because they are a product of supernovae explosions (Matsuura et al ., 2019). As a prime example, cosmic ray ionization of H 2 molecules adsorbed on amorphous ice-coated dust grains can lead to the reaction (Duley, 1996): …”
Section: Water Nanoclustersmentioning
confidence: 99%